Primary Mediastinal Yolk Sac Tumors: An Immunohistochemical Analysis of 14 Cases. Issue 2 (February 2019) - Weissferdt, Annikka; Kalhor, Neda; Rodriguez Canales, Jaime; Fujimoto, Junya; Wistuba, Ignacio I.; Moran, Cesar A.
Abstract : Primary mediastinal germ cell tumors are uncommon tumors that can pose diagnostic difficulties due to their morphologic spectrum and unusual site. Immunohistochemistry plays an increasing role in the diagnosis of these tumors. Whereas the immunophenotype of testicular yolk sac tumors (YST) is rather well known, the opposite is true for primary mediastinal YST leading us to investigate the immunohistochemical features of 14 such neoplasms. Fourteen cases of primary mediastinal YST were reviewed and representative whole tissue sections were selected for immunohistochemical analysis using antibodies directed against CAM5.2, SALL4, OCT3/4, glypican-3, CD30, α-fetoprotein (AFP), CD117, placental alkaline phosphatase (PLAP), GATA-3, and CDX2. The percentage of positive tumor cells and the intensity of staining were evaluated and scored. All cases (100%) showed strong and diffuse expression of CAM5.2 and SALL4, 10 cases (71%) reacted with glypican-3 and AFP in a patchy manner, 5 cases (36%) showed focal positivity with PLAP and GATA-3, 4 cases (29%) showed staining for CDX2, 3 (21%) showed expression of CD117, and a single case was positive for CD30 (7%). None of the cases showed any staining for OCT3/4. Primary mediastinal YST appear to have a similar immunohistochemical phenotype as their testicular counterparts. Coexpression of CAM5.2, SALL4, glypican-3, and AFP provides the best support for YST differentiation; however, it has to be noted that none of these markers is specific for these tumors and immunohistochemical results will always have to be interpreted in the context of morphologic, clinical, and radiologic information.